Adsorption Equilibrium and Kinetics of Anisole/Water Mixture on Molecular Sieve 4A - Zhang, Weijiang; Chen, Yinglai; Xu*, Jiao (Asian Journal of Chemistry, 2014)
In this study, the adsorption equilibrium and kinetics of anisole/water mixture on molecular sieve 4A were investigated experimentally and theoretically. The Langmuir isotherm equation and pseudo-second-order model interpreted the observed experimental data of adsorption equilibrium and kinetics properly. Adsorption mechanism was also indicated by the plot of [-0.4977-ln(1-F)] against time t. The adsorption process was indicated to be thermodynamically favorable, spontaneous and endothermic in nature. The feasibility of dehydrating anisole by adsorbing water on molecular sieve 4A was demonstrated by fixed-bed breakthrough curves.